2007
DOI: 10.1111/j.1743-6109.2007.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Journey into the Realm of Requests for Help Presented to Sexual Medicine Specialists: Introducing Male Sexual Distress

Abstract: Introduction The recent availability of noninvasive pharmacological remedies for male sexual function triggered an exponential increase in the number of men requesting help in the sexuality area. Aim The Italian Society of Andrology explored requests for help, not included in formerly established clinical categories of sexual medicine. Methods A central board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In line with Pescatori et al. [11], there is a risk among these young men of not being properly acknowledged by the medical community and directing themselves towards persistent, or recurrent, sexual distress, or drug‐abuse.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In line with Pescatori et al. [11], there is a risk among these young men of not being properly acknowledged by the medical community and directing themselves towards persistent, or recurrent, sexual distress, or drug‐abuse.…”
Section: Discussionmentioning
confidence: 54%
“…In recent years, the use of PDE5i has become more popular among men without ED to improve their sexual performance. This recreational use has been reported by different authors, especially in young men [7–11]. The purpose of our study was to evaluate the recreational use of PDE5i in a population of men between 18 and 30 years of age through a self‐reported anonymous questionnaire.…”
Section: Introductionmentioning
confidence: 91%
“…In such cases, the subjects, not satisfied with the size of their burred penis, or suffering from poor ejaculatory control despite normal erectile functions, may develop a feeling of sexual inadequacy, possibly leading to erectile difficulties. 3 To our knowledge, this is the first study investigating such aspects in healthy obese male subjects. We found that SD in men with obesity is a common and underestimated condition, affecting 40% of subjects investigated by SDEQ-M questionnaire, in the absence of ED or PE.…”
Section: Discussionmentioning
confidence: 87%
“…2 According to the most recent data in literature, SD may be defined as a reduction/absence of 'sexual health,' which results in a feeling of inadequacy, causing a negative impact on sexual responses, not included in the definition of classical ED or in that of 'unconventional requests.' 3 Inadequacy can originate both from physiological modifications of male sexual functions, or from diseases, that is, dysfunctions, dysfunctional symptoms and dysmorphisms derived from andrological and non-andrological origin, which do not relate to ED (National Institutes of Health Consensus Development Panel definition), but that might also induce ED. Along with requests for situational ED, there are a variety of conditions that do not constitute a classical ED, but may be related with 'inadequate sexual health,' such as the new taxonomy of subclinical ED.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual distress was associated with depression and inversely associated with better communication of sexual needs. This manuscript goes well beyond reporting the simple prevalence of a sexual dysfunction and sets a new standard for epidemiologic studies in sexual medicine [10–15].…”
mentioning
confidence: 99%